2004
DOI: 10.1007/s00203-004-0683-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of the sulfur globule proteins of Allochromatium vinosum: mutagenesis of the sulfur globule protein genes and expression studies by real-time RT-PCR

Abstract: During oxidation of reduced sulfur compounds, the purple sulfur bacterium Allochromatium vinosum stores sulfur in the periplasm in the form of intracellular sulfur globules. The sulfur in the globules is enclosed by a protein envelope that consists of the homologous 10.5-kDa proteins SgpA and SgpB and the smaller 8.5-kDa SgpC. Reporter gene fusions of sgpA and alkaline phosphatase showed the constitutive expression of sgpA in A. vinosum and yielded additional evidence for the periplasmic localization of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 39 publications
3
69
0
Order By: Relevance
“…For the insertional inactivation of Characterization of phenotypes, detection of sulfur species and protein determination. A. vinosum WT and mutant strains were characterized in batch culture experiments essentially as described previously (Prange et al, 2004;Hensen et al, 2006). Cells of A. vinosum, grown photo organoheterotrophically on malate [RCV medium (Weaver et al, 1975)] for 3 days were used as an inoculum for experiments concerned with transformation of sulfide and sulfite.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the insertional inactivation of Characterization of phenotypes, detection of sulfur species and protein determination. A. vinosum WT and mutant strains were characterized in batch culture experiments essentially as described previously (Prange et al, 2004;Hensen et al, 2006). Cells of A. vinosum, grown photo organoheterotrophically on malate [RCV medium (Weaver et al, 1975)] for 3 days were used as an inoculum for experiments concerned with transformation of sulfide and sulfite.…”
Section: Methodsmentioning
confidence: 99%
“…1b). Polysulfides were formed as intermediates in the process (Prange et al, 2004), but are not shown here for better clarity. In the next step, sulfite was generated in the cytoplasm by the Dsr proteins.…”
Section: Oxidation Of Sulfide In a Vinosum Strains Deficient In Soeamentioning
confidence: 99%
See 1 more Smart Citation
“…In sulfur-oxidizing organisms, sulfur is stored in the periplasm for later oxidation in proteincoated sulfur globules. 48 In Allochromatium vinosum, the protein coat includes two paralogs, SgpA and SgpB. Although SgpA and SgpB are paralogous, they do not co-occur together in the same operon, thus evading detection by the criteria employed.…”
Section: Further Examplesmentioning
confidence: 99%
“…The photolithoautotrophic growth of A. vinosum wild-type and mutant strains was examined in batch culture under continuous illumination essentially as described by Prange et al (52) in a medium containing sulfide as the sole sulfur compound. Two hundred fifty milliliters of a photoheterotrophically grown stationary-phase culture was harvested (5,900 ϫ g; 10 min), and the cell material was used to inoculate 1 liter of modified Pfennig's medium (17) in a temperaturecontrolled fermentor.…”
mentioning
confidence: 99%